Challenges in waste management at the household level in settlements along the Sario River as the source of marine debris to Manado Bay, Indonesia - Veronika A. Kumurur; Jane M. Mamuaja; Markus T. Lasut; Veibe Warouw (Universitas Sam Ratulangi, 2022)
Marine debris mitigation should be conducted thoroughly especially in the level where they are originated, which is household and settlement areas. In developing countries, waste management in household level has been a challenge because it has never been done properly. This study aims to evaluate the content and the application of waste management guidelines in settlement areas along the river, to assess the level of understanding of each head of family in using the guidelines and to assess the awareness level in doing the waste management. There are two aspects of waste management in household level: 1) waste management mechanisms, and 2) awareness of each head of family in was management. Mechanism aspect of waste management consists of two components. They are (1) guidelines in management mechanisms (which consists of guideline content and level of understanding-compliance) and (2) implementation of management mechanisms. Awareness aspect of each head of family in conducting waste management were assessed based on three components, they are 1) knowledge, 2) concern, and 3) willingness. A number of 249 households (from a total 453 who live in both sides of the river) were interviewed (as respondents) and they were chosen randomly. The respondent was those with family (parents and children) and the head of the household. The interview was conducted using a questionnaire, which content several questions related to the assessed aspects. The data was quantitatively analysed using a simple Statistics obtain percentages. The result shows that the a detailed content of guidelines on how to properly manage the was not found, the level of understanding on waste management was still low, the implementation of waste management in the level of household has not been done properly, and the willingness to share the finance in waste management is also low. It is then concluded that waste management at the household level in the regions faces various challenges. The best choice in waste management aspect at the household level is given in in this paper.